Novel treatment options in depression and psychosis - Ceskova E (Dove Medical Press, 2018)
Eva Ceskova, Petr Silhan Department of Psychiatry, University Hospital Ostrava, Ostrava, Czech Republic Abstract: In spite of tremendous development in central nervous system research, current treatment is suboptimal, especially in severe mental disorders. In medicine, there are two main methods of improving the health care provided: seeking new treatment procedures and perfecting (optimizing) the existing ones. Optimization of treatment includes not only practical tools such as therapeutic drug monitoring but also implementation of general trends in the clinical practice. New pharmacological options include new more sophisticated forms of monoaminergic drugs, old drugs rediscovered on the base of a better understanding of pathophysiology of mental illnesses, and drugs aimed at new treatment targets. In depression, treatment resistance to antidepressive pharmacotherapy represents one of the most important clinical challenges. Switching to monotherapy with new multimodal/multifunctional antidepressants and augmentation with new atypical antipsychotics (aripiprazole and brexpiprazole) may be promising options. Further, current evidence supports utility and safety of adjunctive treatment of nutraceuticals. Novel approaches being studied include ketamine and opioids. Recent advances in technology and emerging knowledge about dysfunctional brain circuits and neuroplasticity have led to the development of different new neuromodulation techniques usually used as add-on therapy. Antipsychotics are still the cornerstone of the current treatment of schizophrenia. Two new partial dopamine agonists, brexpiprazole and cariprazine, are now available in addition to aripiprazole. Although the mechanisms of action are similar, the two agents differ in terms of their pharmacodynamic profiles. Further, two new formulations of long-acting injections of second-generation antipsychotics (aripiprazole lauroxil and 3-month paliperidone palmitate) were introduced into clinical practice. New treatment options not yet available include cannabidiol, glutamate modulators, and nicotine receptors agonists. Keywords: optimization of treatment, multimodal/multifunctional antidepressants, partial dopamine agonists, glutamate modulators, nicotine receptors agonists